BUSINESS LAW IN THE ERA OF ARTIFICIAL INTELLIGENCE (AI): BALANCING INNOVATION AND PROTECTION FOR GENERATION Z - Imelda Mardayanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The rapid advancement of Artificial Intelligence (AI) has transformed the business landscape in Indonesia, offering opportunities for innovation while posing legal and ethical challenges. Generation Z, as digital natives, is at the forefront of AI's impact, benefiting from enhanced productivity and personalization but also facing risks such as job automation, privacy breaches, and digital consumerism. This study analyzes Indonesia's legal framework for AI in business, focusing on the Electronic Information and Transactions Law (UU ITE), Personal Data Protection Law (UU PDP), and the Ministry of Communication and Informatics Circular No. 9/2023 on AI Ethics. Using a normative qualitative approach and literature review, the research evaluates the effectiveness of existing regulations, identifies legal gaps, and examines AI's implications for Generation Z in business, employment, and digital consumption. Findings reveal that current regulations are fragmented and non-binding, leaving vulnerabilities in data protection, algorithmic accountability, and ethical compliance. Recommendations include developing a comprehensive AI-specific law, enhancing digital literacy for Generation Z, and strengthening regulatory oversight to balance innovation with protection.